Factors Influencing The Optimization Of Organizational Sustainable Performance: A Case Study Of Pt. Mulia Realty Batindo In Batam, Indonesia - Selvaraju, Gayathri (2014)
Organizational sustainable performance is fast becoming a critical strategic objective for any growing organizations and thus improving and sustaining the organizational performance is vastly becoming an integral part to the corporate world. The purpose of this case study is to identify the factors influencing the optimization of organizational sustainable performance in PT. Mulia Realty Batindo at Batam, Indonesia. The performance management system of the organization is analyzed to find the weaknesses in the system that is providing the limitations and challenges to the organization,